HUKUM ADAT DALAM PEMBAGIAN WARIS TERHADAP MASYARAKAT BUGIS - Attahariq T.P; Azizul Hakim .C (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Customary law is one of the important sources of law in the development of national law which leads to statutory regulations. Bugis tribe is one of the four tribes in South Sulawesi. In the case of inheritance, Bugis tribe recognizes parental kinship system. One of the core elements of customary law for the development of national inheritance law is customary inheritance law. The research results show that the distribution of inheritance to the Bugis community is carried out in three ways:grants, testament or last testament and testament, and after the testator dies.